The Decision to Privatize: Finance and Politics - DINC, I. SERDAR; GUPTA, NANDINI (Journal of Finance, 2011)
ABSTRACT We investigate the influence of political and financial factors on the decision to privatize government‐owned firms. The results show that profitable firms and firms with a lower wage bill are likely to be privatized early. We find that the government delays privatization in regions where the governing party faces more competition from opposition parties. The results also suggest that political patronage is important as no firm located in the home state of the minister in charge is ever privatized. Using political variables as an instrument for the privatization decision, we find that privatization has a positive impact on firm performance.